DETERMINANTS OF MARKET ENTRY: A STUDY ON TURKISH MANUFACTURING INDUSTRY (1996-2001 PERIOD) - BALCI İZGİ, Berna; DİNERİ, Eda (Acta Universitatis Lodziensis. Folia Oeconomica, 2015)
In this article we study on determinants of market entry behaviour of 60 four-digit Turkish manufacturing industry for the 1996-2001 period. We estimated a model using GMM (Generalised Method of Moments). The results show industry growth rate and exports are important to determine entry behaviour for the period and the previous period’s entry is effective on current entries. The entry and exit rates of the firms were taken from Turkish Statistical Institute’s (TIS) resources and changed from SIC Rev 3 to SIC Rev 2. The other variables were taken from SIC Rev 2. The reason why the data were limited to the year 2001 is advertising expenditures were not available. The data includes all the state and private firms that employ 10 workers and above.